2016
DOI: 10.1007/s00345-016-1813-7
|View full text |Cite
|
Sign up to set email alerts
|

National trends and differences in morbidity among surgical approaches for radical prostatectomy in Germany

Abstract: RP utilization in Germany is dropping, but the use of MIRP has risen steadily during the years 2005-2012, which is expected to have a positive impact on the morbidity of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…While numerous investigators have reported complications after RP, most of them lacked standardised reporting systems, which are essential for quality management, as well as for comparison across approaches or institutions [2,3]. As such, the Martin and Clavien-Dindo criteria are commonly relied on [2,4,5] Published in 2002, Martin et al [2] developed 10 criteria for accurate and assisted laparoscopic prostatectomy (RALP) has been broadly adopted in the USA and Europe [6][7][8][9]. Despite the rapid spread of RALP, to date, only few retrospective data compared the two approaches with regard to complications using standardised reporting systems [6,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous investigators have reported complications after RP, most of them lacked standardised reporting systems, which are essential for quality management, as well as for comparison across approaches or institutions [2,3]. As such, the Martin and Clavien-Dindo criteria are commonly relied on [2,4,5] Published in 2002, Martin et al [2] developed 10 criteria for accurate and assisted laparoscopic prostatectomy (RALP) has been broadly adopted in the USA and Europe [6][7][8][9]. Despite the rapid spread of RALP, to date, only few retrospective data compared the two approaches with regard to complications using standardised reporting systems [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, RP has been performed using an open approach (ORP). Nevertheless, over the past decade, robot‐assisted laparoscopic prostatectomy (RALP) has been broadly adopted in the USA and Europe . Despite the rapid spread of RALP, to date, only few retrospective data compared the two approaches with regard to complications using standardised reporting systems .…”
Section: Introductionmentioning
confidence: 99%
“…Over 90 000 RPs are performed per year in the USA 30 and about 25 500 in Germany. 31 Due to this high volume, even small differences in surgical outcomes can possibly affect a great number of patients. Therefore, we aim to increase the level of evidence concerning the optimal suture techniques for VUA.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PCa in China is much lower than that in western countries but has increased dramatically in recent years [ 4 ]. Satisfactory therapeutic effects for PCa at early stage can be achieved through RP, including ORP, LRP, and RARP [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%